2010
DOI: 10.2176/nmc.50.355
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Focus Stimulation and Seizure Control in the Rat Model of Kainic Acid-Induced Limbic Seizures

Abstract: The inhibitory effects of deep brain stimulation (DBS) were investigated in a rat model of kainic acid (KA)-induced limbic status epilepticus. Wistar rats were injected with 1.0 mg KA into the left amygdala after stereotactic implantation of a guide cannula and electrodes. Bipolar rectangular pulses of 0.1 msec duration and 0.1-0.3 mA amplitude were applied intermittently to the left amygdala (10 Hz or 130 Hz), left ventral hippocampus (10 Hz), and left dorsomedial thalamus (130 Hz). Seizure frequency was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The mediodorsal thalamic nucleus is thought to be involved in the modulation of seizures, specifically those involving limbic regions (Bertram et al, 1998(Bertram et al, , 2001. Previous clinical studies showed that electrical stimulation in MT can decrease seizure frequency (Sterman et al, 1982;Urino et al, 2010), and these results demonstrated that MT activities are involved in blocking seizures. Yet, the mechanisms by which thalamic stimulation through deep brain stimulation may reduce seizure frequency are not clear.…”
Section: Discussionmentioning
confidence: 98%
“…The mediodorsal thalamic nucleus is thought to be involved in the modulation of seizures, specifically those involving limbic regions (Bertram et al, 1998(Bertram et al, , 2001. Previous clinical studies showed that electrical stimulation in MT can decrease seizure frequency (Sterman et al, 1982;Urino et al, 2010), and these results demonstrated that MT activities are involved in blocking seizures. Yet, the mechanisms by which thalamic stimulation through deep brain stimulation may reduce seizure frequency are not clear.…”
Section: Discussionmentioning
confidence: 98%
“…The acquired chronic epileptic state in this rat model for TLE makes it a good model to study the effects of anti-epileptic treatments on the occurrence rate of spontaneous epileptic seizures. Several preclinical studies investigating the effect of high frequency hippocampal DBS are performed in animal models where seizures are evoked either after kindling stimuli [4,5], or after injection of chemo-convulsants [6,7,32]. Only a few pre-clinical studies have investigated the effect of hippocampal DBS on the occurrence of spontaneous seizures in the chronic epileptic state [3,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Following injection of kainic acid into rat amygdala, producing acute status epilepticus, 10 Hz stimulation of the amygdala and 130 Hz stimulation of the dorsal thalamus inhibited seizures, but 10 Hz ventral hippocampal stimulation had no effect (Urino et al, 2010). Following injection of kainic acid into rat amygdala, producing acute status epilepticus, 10 Hz stimulation of the amygdala and 130 Hz stimulation of the dorsal thalamus inhibited seizures, but 10 Hz ventral hippocampal stimulation had no effect (Urino et al, 2010).…”
Section: Hippocampal Stimulation For Epilepsy: Animal Studiesmentioning
confidence: 97%